2020
DOI: 10.2196/preprints.17703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Untold Stories in User-Centered Design of Mobile Health: Practical Challenges and Strategies Learned From the Design and Evaluation of an App for Older Adults With Heart Failure (Preprint)

Abstract: BACKGROUND User-centered design (UCD) is a powerful framework for creating useful, easy-to-use, and satisfying mobile health (mHealth) apps. However, the literature seldom reports the practical challenges of implementing UCD, particularly in the field of mHealth. OBJECTIVE This study aims to characterize the practical challenges encountered and propose strategies when implementing UCD for mHeal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…Users' concerns are not necessarily focused on mere usability issues and testing of existing features, often of a certain service or application, that is often the focus in user studies (e.g. Cornet et al, 2020;Gould & Lewis, 1985;Stojmenova, Imperl, Žohar & Dinevski, 2012). By using open-ended questions, respondents are allowed to innovate freely and propose ideas that go beyond specific services; hence, the answers can also be useful for informing the development of multiple types of services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Users' concerns are not necessarily focused on mere usability issues and testing of existing features, often of a certain service or application, that is often the focus in user studies (e.g. Cornet et al, 2020;Gould & Lewis, 1985;Stojmenova, Imperl, Žohar & Dinevski, 2012). By using open-ended questions, respondents are allowed to innovate freely and propose ideas that go beyond specific services; hence, the answers can also be useful for informing the development of multiple types of services.…”
Section: Discussionmentioning
confidence: 99%
“…By using open-ended questions, respondents are allowed to innovate freely and propose ideas that go beyond specific services; hence, the answers can also be useful for informing the development of multiple types of services. As it has been found that lack of resources hinder cooperation between end-users and software developers (Rytkönen, Kinnunen & Martikainen, 2022), and usercentered design approaches usually include several phases such as planning, designing, testing and evaluating, requesting longer time spans and hence more resources (Cornet et al, 2020;Gould & Lewis, 1985;Stojmenova, Imperl, Žohar & Dinevski, 2012;van Velsen, Ludden, & Grünloh, 2022), the option of including open-ended questions in larger studies related to eHealth information behavior can be a cost-effective way to provide developers with useful feedback. The approach can be termed as a form of citizen science (van Velsen, Ludden, & Grünloh, 2022) with a major benefit of not requiring a recruiting of end-users at certain points of time at certain places, or the effort of testing existing services thoroughly multiple times (Cornet et al, 2020;Gould & Lewis, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…4. According to [81], mHealth projects frequently involve distinct stakeholders such as patient populations (e.g., older adults, patients with chronic conditions) and clinician experts, or both.…”
Section: B Design Target Populationmentioning
confidence: 99%
“…However, the practical challenges and pitfalls of these approaches are seldomly reported in published literature (Cornet, Toscos, et al, 2020). Challenges can come in formative, design, and evaluation stages or as recurrent processes (Cornet, Toscos, et al, 2020).…”
Section: Research and Development Approaches To Aid Value Sensitive D...mentioning
confidence: 99%
“…However, the practical challenges and pitfalls of these approaches are seldomly reported in published literature (Cornet, Toscos, et al, 2020). Challenges can come in formative, design, and evaluation stages or as recurrent processes (Cornet, Toscos, et al, 2020). On top of that, to validate value sensitive eHealth, it will be necessary to test the differences in actual effectiveness trials.…”
Section: Research and Development Approaches To Aid Value Sensitive D...mentioning
confidence: 99%